1993
DOI: 10.1016/0014-5793(93)80118-e
|View full text |Cite
|
Sign up to set email alerts
|

Participation of cathepsin L on bone resorption

Abstract: The proteinase responsible for bone collagen degradation in osteo-resorption was examined. The bone pit formation induced by parathyroid hormone (PTH) was markedly suppressed by leupeptin, E-64 and cystatin A, while no inhibition was observed by CA-074, a specific inhibitor of cathepsin B. Pig leucocyte cysteine proteinase inhibitor (PLCPI), a specific inhibitor of cathepsin L, and chymostatin, a selective inhibitor of cathepsin L, completely inhibited the pit formation. Cathepsin L activity in osteoclasts was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 28 publications
1
62
0
Order By: Relevance
“…The soluble fraction was removed and co-incubated with 20 M N-CBZ-Phe-Arg-7-amido-4-methylcoumarin (Sigma), a substrate for cathepsins B and L, at 37°C for 10 min. To determine the specific contributions of the two proteases, other tubes were supplemented with 0.75 M CA-074 (Peptides International, Louisville, KY), a specific inhibitor of cathepsin B (Kakegawa et al, 1993;Inubushi et al, 1994). The activity of cathepsin L, determined as the fraction insensitive to CA-074, was completely suppressed when 0.25 M chymostatin (Sigma) was added to the assay.…”
Section: Methodsmentioning
confidence: 99%
“…The soluble fraction was removed and co-incubated with 20 M N-CBZ-Phe-Arg-7-amido-4-methylcoumarin (Sigma), a substrate for cathepsins B and L, at 37°C for 10 min. To determine the specific contributions of the two proteases, other tubes were supplemented with 0.75 M CA-074 (Peptides International, Louisville, KY), a specific inhibitor of cathepsin B (Kakegawa et al, 1993;Inubushi et al, 1994). The activity of cathepsin L, determined as the fraction insensitive to CA-074, was completely suppressed when 0.25 M chymostatin (Sigma) was added to the assay.…”
Section: Methodsmentioning
confidence: 99%
“…Pathologic cells may also secrete large amounts of cathepsin L, as observed in cultures of malignantly transformed cells (12). Of particular interest is the evidence of cathepsin L secretion at sites of normal bone resorption (13)(14)(15)(16), as well as elevated levels of cathepsin L in the synovial fluid of RA patients (17).…”
mentioning
confidence: 99%
“…Vaes et al have shown that several inhibitors of cysteine proteinases, such as leupeptin, antipain, tosyl-lysyl chloromethane (TosLys-CH,Cl), benzyloxycarbonyl-phenylalanyl-alanyl-diazomethane (Z-Phe-Ala-CHN,) and E-64, markedly inhibited PTH-induced bone resorption in cultured mouse bone cells [4-61. Moreover, we reported that the bone pit formation induced by PTH was-strongly suppressed by PLCPI, a specific inhibitor of cathepsin L and/or L-like proteinase, and chymostatin, a selective inhibitor of cathepsin L, while no inhibition was observed by CA-074, a specific inhibitor of cathepsin B [13]. However, so far, there has been no apparent evidence that cathepsin L and/or L-like proteinase are secreted from the cells induced by PTH.…”
Section: Regulation Of Cysteine Proteinase Secretion By Pth and Calcimentioning
confidence: 99%
“…Rat osteoclasts were purified according to the method of Tezuka et al as described previously [13]. After purification, 90% of cells were multinucleate and had tartrate-resistant acid phosphatase activity.…”
Section: Cysteine Proteinase Activity In Rat Osteoclasts and Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation